Aspects Regarding the Voting System in Romania in the Modern Era (19th Century) - Gudin, Cristina (Acta humanitarica academiae Saulensis, 2025)
The study aims to present the evolution of the voting system in Romania during the 19th century, highlighting the social and political context that led to the transition from one stage to the next. In the modern era, in Romania, the participation in the political life of the inhabitants was conditioned by the economic situation, citizenship, gender, age, and legal record. Thus, the right to vote was granted only to men who had reached the age of 21 and who were engaged in honorable and profitable economic activities. The possession of citizenship by birth or naturalization was added, as well as the condition of not having seriously violated the laws of the country. Although the electoral body was small and the rural population was poorly politically represented, even though it was the most numerous, exceeding 80% of the total population of Romania, it can be stated that, in general, there is a tendency to increase the number of voters. This was achieved in several moments, by reducing the electoral census, but also by expanding the number of professions whose practice ensured voting attendance without fulfilling the economic conditions. These exceptions were based on the fact that the practitioners of the respective professions (generally freelancers) were sufficiently educated and politically mature to be able to make a conscious and informed choice without falling victim to manipulation. These, as well as other aspects (such as women getting the right to vote), will be developed in the study.